Short-Term Prognostic Factors in Hospitalized Herpes Zoster Patients and Its Associated Cerebro-Cardiovascular Events: A Nationwide Retrospective Cohort in Japan - Ishikawa, Yuichi; Nakano, Kazuhisa; Tokutsu, Kei; Nakayamada, Shingo; Matsuda, Shinya; Fushimi, Kiyohide; Tanaka, Yoshiya (Frontiers in Medicine, 2022)
Background Short-term mortality and incidence of cerebrovascular and cardiovascular events (C-CVE) during hospitalization of patients with severe herpes zoster (HZ) have not been sufficiently investigated. We aimed to investigate short-term prognosis and incidence of C-CVE associated with HZ in hospitalized patients. Methods This retrospective cohort study from April 2016 to March 2018 included HZ inpatient cases selected from the Diagnosis Procedure Combination database—a Japanese nationwide inpatient database. HZ and C-CVE were diagnosed based on the 10th revision of the International Classification of Diseases and Injuries codes. The definition of primary exposure was that treatments were initiated within 7 days of admission, and antivirals were administered for ≥7 days. Main Outcomes were in-hospital deaths and C-CVE onset after hospitalization. Results Among 16,811,501 in-hospital cases registered from 1,208 hospitals, 29,054 cases with HZ were enrolled. The median age was 71.0 years, 15,202 cases (52.3%) were female, and the HZ types were the central nervous system (n=9,034), disseminated (n=3,051), and ophthalmicus (n=1,069) types. There were 301 (1.0%) in-hospital deaths and 385 (1.3%) post-hospitalization onset of C-CVE. The 30-day in-hospital survival rates with or without underlying disease were 96.8% and 98.5%, respectively. Age ≥75 years (hazard ratio [HR], 2.18; 95% confidence interval [CI], 1.55–3.05), liver cirrhosis or hepatic failure (HR, 5.93; 95% CI, 2.16–16.27), chronic kidney disease (HR, 1.82; 95% CI, 1.24–2.68), heart failure (HR, 1.65; 95% CI, 1.22–2.24), and old cerebrovascular events (HR, 1.92; 95% CI, 1.10–3.34) were associated with poor short-term prognosis. Age ≥75 years (odds ratio [OR], 1.70; 95% CI, 1.29–2.24), diabetes (OR, 1.50; 95% CI, 1.19–1.89), dyslipidemia (OR, 1.95; 95% CI, 1.51–2.51), hyperuricemia (OR, 1.63; 95% CI, 1.18–2.27), hypertension (OR, 1.76; 95% CI, 1.40–2.20), heart failure (OR, 1.84; 95% CI, 1.32–2.55), and glucocorticoid administration (OR, 1.59; 95% CI, 1.25–2.01) were associated with increased risks for in-hospital C-CVE onset. Conclusions The underlying diseases that could influence the short-term mortality of severe HZ were identified. Glucocorticoid is a possible risk factor for the in-hospital onset of C-CVE after severe HZ development.